Post-Pandemic Covid-19 Analysis: The Effect of Distance Learning Toward Learning Loss in Primary School - Resti Yektyastuti; Muhammad Rendi Ramdani; Gugun Gunadi; Annisa Mawardani; Ramdiani Nurohmah (AL-ISHLAH: Jurnal Pendidikan, 2023)
The spread of the Corona Virus Pandemic virus Disease 19 (COVID-19) resulted in the learning process in their respective homes. This impacts students' psychology and reduces the quality of students' skills, which is then suspected of learning loss. This research aimed to analyze the relationship between distance learning methods and the numeracy learning loss of elementary school students in high grades. This quantitative research uses a simple correlation method toward 150 elementary school students. Determination of the sample using a purposive sampling technique. The independent variable in this study is the distance learning method (X), and the dependent variable is the loss of learning numeracy (Y).  Data were analysed by correlation test (Pearson Correlation), determination of the correlation coefficient with the R square model and t-test. Pre-analysis test includes a normality test using Kolmogorov Smirnov. The instrument in this research is questionnaires with a Likert scale. The research analysis results show a positive relationship between the independent variable (distance learning method) and the dependent variable (learning loss of numeration). Based on the coefficient of determination, the effect size is 46.2%, while the other 54.8% is affected by other factors besides the learning method.